Building resilient agricultural system through groundwater management interventions in degraded landscapes of Bundelkhand region, Central India - Singh, R.; Garg, K. K.; Anantha, K. H.; Akuraju, V.; Dev, I.; Dixit, S.; Dhyani, S. K. (Elsevier, 2021)
The study was carried out at community scale watershed in one of the fragile ecologies of Central India.